FIXED-DOSE COMBINATIONS IN THE TREATMENT OF HYPERTENSION IN THE RUSSIAN FEDERATION. (April 2021) - Vladimir, Kutsenko; Balanova, Yulia; Shalnova, Svetlana; Imaeva, Asiia; Kapustina, Anna; Muromtseva, Galina; Evstifeeva, Svetlana; Karamnova, Natalya; Maksimov, Sergey; Yarovaya, Elena
Abstract : Objective: To estimate the frequency of fixed-dose combinations (FDC) of antihypertensive medications (AHM) in the hypertension treatment in the population of the Russian Federation (RF). Figure. No caption available. Design and method: A cross-sectional study 'Epidemiology of Cardiovascular Diseases in the RF (ESSE-RF)' was performed in 13 regions (2012–2013). Randomly selected males (N = 8304) and females (N = 13464) aged 25–64 were included (response rate>80%). Standard epidemiology methods and criteria were used. Hypertension defined as a measured blood pressure (BP) of 140/90 mm Hg or greater and/or treatment with AHM. The structure of FDC in AHM was investigated. AHM have been analyzed by the following classes: diuretics (D), betablockers (BB), calcium antagonists (CA), angiotensin converting enzyme inhibitors (ACEi), angiotensin II receptor blockers (ARBs), and «other». In addition, FDC of AHM have been studied. Statistical data was processed using R 3.6.1 (R Foundation for Statistical Computing, Vienna, Austria). Results: Results The prevalence of hypertension and treatment in the RF was 45, 7% and 51.8%. Among hypertensive patients who were receiving treatment, 65.6% were taking 1 AHM, 2 – 23.1%, 3 and more – 6.7%, whereas 4, 6% were taking non-AHM. The most commonly taken medications were ACEi (58.4%), BB (34.9%), and D (32.4%) The frequency of taking an FDC of AHM was 15.6%. Among those taking FDC the most frequently employed were D+ACEi (49.3%), D+ARBs (24.8%), and D+BB (17.2%) fig 1. Conclusions: Despite the importance of BP control in preventing cardiovascular and cerebrovascular events, only 1/3 of hypertensive patients in the RF have their BP under control. Prescription frequency of an FDC of AHM remains low – only every sixth patient with hypertension taking medications applied the FDC.